An Empirical Study of Recent Mainland Chinese Migration to Vancouver - Yu, Li (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractOne of the major changes in the last decade in the character of Chinese migration to Vancouver and to Canada as a whole is that mainland Chinese migrants have become the largest source of Chinese immigrants arriving in Canada. In Vancouver, mainland Chinese migrants have become the largest group within the Chinese Canadian community. This paper explains the historical background for the change and analyzes the motivations behind mainland Chinese migration to Vancouver and British Columbia. It points out that most recent migrants from mainland China have come from a middle class background. Poverty, family union, and political dissent are no longer major driving forces in peoples’ decisions to migrate. In the 1990s and 2000s, mainland migrants have sought to better their natural and social environments, and to achieve a higher quality of life for themselves and their children. Prospective migrants to Canada view the existence of a large Chinese community in Vancouver as an important attraction, providing new immigrants with certain conveniences in everyday life and various job opportunities.